RANCANG BANGUN SISTEM INFORMASI GEOGRAFIS PENGUASAAN PEMILIKAN PENGGUNAAN DAN PEMANFAATAN TANAH (P4T) KABUPATEN JEMBRANA BERBASIS WEB - Agus Swastika, I Putu; Ana Widiatmika, I Made Agus; Eka Wiadi, Putu (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi, 2012)
As we all know that in this era of globalization is the rapid advances in technology at all. Lots of research being done to encourage the emergence of new discoveries in the world of technology, especially information technology. As one of the event was or Geographic Information System geographic information system (GIS). Land policy in one of the principle of management by the Head of National Land Agency (2007) which contribute significantly in increasing order of life with a more equitable and dignified in relation to the control, pernilikan, use and utilization of land (P4T) (Strategic Plan of National Land Agency of the Republic Indonesia 2007-2009). Problems that often occurs regarding control, ownership, use and utilization of an area of land due to lack of land administration tertibnya. To realize the condition of orderly land administration needed a big effort and long-term nature. Through the inventory data acquisition, possession, use and utilization of land that would be expected to land database issues encountered will be overcome with good.
Keywords: Geographic information systems, land.